Frindle - Clements, Andrew (New York, NY, 1996)
When he decides to turn his fifth grade teacher's love of the dictionary around on her, clever Nick Allen invents a new word and begins a chain of events that quickly moves beyond his control.
Texas Bluebonnet Award 1998